A revision of the Australian species of Trimma (Actinopterygii, Gobiidae), with descriptions of six new species and redescriptions of twenty-three valid species - Winterbottom, Richard; Hoese, Douglass F. (Zootaxa, 2015)
The gobiid genus Trimma currently contains 75 valid species, with another 20–30 known but undescribed species. There are 29 species in Australian waters (six undescribed). This paper describes the six new species, and provides redescriptions of most of the 23 previously described species known from the region, as well as a key for all the species. The six new species are: T. insularum (endemic to Cocos (Keeling) Islands), T. kitrinum (Fiji to Great Barrier Reef), T. meristum (Cape York to the Bismark Archipelago and Fiji), T. pentherum (Great Barrier Reef to Fiji and the South-West Islands of Palau), T. readerae (Australia to Japan), and T. xanthum (Palau to Fiji, Great Barrier Reef to Christmas Island). The following 23 species have been recorded from Australian waters, and most are redescribed here: T. anaima (Comores to Fiji), T. annosum (Maldives to the Phoenix Islands, Taiwan to the southern Great Barrier Reef), T. benjamini (southern Vietnam to the Marshall Islands, Samoa and southern Barrier Reef), T. caesiura (Ryukyus through the Marshall Islands to Samoa and Elizabeth Reef on the Lord Howe Rise), T. capostriatum (New Caledonia to eastern Australia and Papua New Guinea), T. maiandros (Java to the Ryukyus, Marshalls to Great Barrier Reef), T. emeryi (Comores to Ryukyus and Samoa), T. fangi (western South China Sea through to the Solomons), T. flavatrum (Ryukyu Islands to Western Australia and Samoa), T. hoesei (Chagos Archipelago, central Indian Ocean to Palau and Solomons), T. lantana (Australia, Solomons, northern New Guinea, South-West Islands of Palau), T. macrophthalmus (Ryukyu Islands to Cocos (Keeling) Islands and Samoa), T. milta (Taiwan to Western Australia, Society Islands and Hawaii), T. nasa (Sumbawa, Indonesia to Fiji), T. necopinum (northern tip of Cape York to Sydney), T. nomurai (Japan to northern Australia and New Caledonia), T. okinawae (western Thailand to Japan and the Phoenix Islands, north-west Australia to the Great Barrier Reef), T. preclarum (Palau to Fiji, Great Barrier Reef), T. stobbsi (Maldives to New Caledonia), T. striatum (Maldives to Palau, to northern Australia), T. taylori (Red Sea to Hawaii and Society Islands), T. tevegae (Red Sea to Ryukyu Islands, Marshall Islands to Samoa), and T. unisquame (Comores to Hawaii and Easter Island).